Pengaruh Senam Kegel Terhadap Dispareunia pada Perempuan Menopause di Kelurahan Pamoyanan Wilayah Kerja Puskesmas Pasirkaliki Bandung - Gurid mulyo; Iryanti .; Susy Hermaningsih (Poltekkes Kemenkes Bandung, 2014)
Kegel exercise is an intervention which can be carried out by menopause women suffering dyspareunia in order to avoid the risk of depression. This research is aimed at identifying the impacts of Kegel exercise on menopause women with dyspareunia at Pamoyanan District in the Operational Area of Pasirkaliki Community Health Center in Bandung. The result of this research can be used to improve the service quality and model for the community so as to improve the life quality of menopause women. The type of this research is quasi experiment with pre - post test one group design. Independent variable in this research is Kegel exercise, while the dependent variable is dyspareunia. Based on the sampling technique, namely, consecutive sampling, there are 36 respondents. Dyspareunia scale is measured by using the instrument of numeric scale from 0-10. After the measurement of dyspareunia scale prior to the Kegel exercise (pre test), menopause women carry out Kegel exercise 3 times a day, namely in the morning, afternoon and evening, for 6 weeks which is monitored through a log book, and subsequently, dyspareunia scale is measured following the Kegel exercise (post test). The analysis of data in order to find out the average of dyspareunia scale before and after Kegel exercise is conducted by using univariate analysis, while in order to find out the impact of Kegel exercise on dyspareunia, T dependent test is carried out. The results of analysus indicate that the average dyspareunia scale before Kegel exercise (pre test) is 5.58 and the average dyspareunia scale after Kegel exercise (post test) is 2.69, which indicate the decreased dyspareunia scale in the amount of 2.89 points. The result of the statistic test indicates that t value = 12.665 with p-value = 0.000 < a (0.05), which means that Kegel exercise carried out for 6 weeks has decreased dyspareunia on menopause women. Therefore, menopause women with dyspareunia should carry out Kegel exercise as a therapy so that they can avoid the effects of the decrease in estrogen and estrogen therapy, thus their life quality will be improved